The state of Business Intelligence : in Finnish enterprises - Nykänen, Erno (2015)
Business Intelligence (BI) has recently been of interest both in information technology and accounting fields of research. This owes at least partly to how organisations today have increasing amounts of data and information at their disposal and they are attempting to reap benefits and competitive advantage from them. This study focuses on large Finnish enterprises and examines how they are applying business intelligence today. Especially the process nature of transforming data in to knowledge is under scrutiny and how BI is utilized in decision making. The results indicate that organisations are perceiving benefits from utilising their BI processes and while the technological factors are of importance, organisational factors such as top management support and organisational culture have potentially even larger effect on the benefits that the organisation perceives. For individual users, BI improves their speed and quality of decision making and they utilise BI quite frequently in the decision making process. While some are still relying on spreadsheet-applications for their BI needs, other – more specialised and advanced – analysis and visualisation tools are also being widely adopted and used.